The impact of Off-Balance sheet credit exposure on bank performance in Vietnam - Dieu Thi Thanh Tran; Ha Thi Thu Phan (My University, 2019)
The impact of Off-Balance sheet credit exposure on bank performance in Vietnam
Keywords: Off-balance sheet; Bank performance; Vietnam